Design of a clinical competency committee to maximize formative feedback - Anthony A. Donato; Richard Alweis; Suzanne Wenderoth (Greater Baltimore Medical Center, 2016)
Background: As the next phase in the roll-out of Next Accreditation System, US residency programs are to develop Clinical Competency Committees (CCCs) to formally implement outcome-based medical education objectives in the resident assessment process. However, any changes to an assessment system must consider balancing formative and summative tensions, flexibility and standardization tensions, fairness and transparency to learners, and administrative burden for faculty. Objectives/Methods: In this article, one program discusses the approach one internal medicine residency took to create a developmental model CCC. In this model, a learner's mentor presents the argument for competence to the CCC, while a second reviewer presents challenges to that argument to the rest of the committee members. The CCC members provide other insights and make recommendations. The mentor presents the final committee recommendations to that resident, who then works with the mentor to develop a plan for future action. Results: CCC second reviewers spent an average of 30.4 min (SD: 11.4) preparing for each resident's discussion, a duty performed 5-7 times every 6 months. Faculty development was associated with an increase in the number of action-oriented comments in the meeting minutes (3.2-4.1 comments per resident, p=0.001). CCC members and mentors gave higher Likert-type ratings than residents for fairness (4.8 vs. 4.0) and learning prioritization (4.7 vs. 4.2), but similar ratings for transparency (4.0 vs. 4.2). Conclusion: Developmental model CCCs may be feasible for residency programs, but faculty development may be necessary.